If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 8) + 4(x + 9) = 2x Reorder the terms: -3(8 + x) + 4(x + 9) = 2x (8 * -3 + x * -3) + 4(x + 9) = 2x (-24 + -3x) + 4(x + 9) = 2x Reorder the terms: -24 + -3x + 4(9 + x) = 2x -24 + -3x + (9 * 4 + x * 4) = 2x -24 + -3x + (36 + 4x) = 2x Reorder the terms: -24 + 36 + -3x + 4x = 2x Combine like terms: -24 + 36 = 12 12 + -3x + 4x = 2x Combine like terms: -3x + 4x = 1x 12 + 1x = 2x Solving 12 + 1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 1x + -2x = 2x + -2x Combine like terms: 1x + -2x = -1x 12 + -1x = 2x + -2x Combine like terms: 2x + -2x = 0 12 + -1x = 0 Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 14+6M-2-3M=5M+8 | | 5x^2-10x+6y^2+36y+60=0 | | 5w^2=35w | | 12m-2m+3+4m=31 | | 12-2m+3+4m=31 | | 9v^2+9v-40=0 | | 6+8m+8=12m+2+4 | | 6+8m=12m+2+4 | | 8(m+4)(2m-1)= | | 9x+4x=0.9-1.4 | | 3M+15=5m+9 | | 5M+40=100 | | 100=5M+40 | | 151=7x-6(-3x+4) | | 2x-3.4=x-3.6 | | 2xy=x^6+y^6 | | 57.6=240(0.03)t | | 3x-13+4x-24=180 | | 1half(6x-8)=41 | | 3x-13=4x-24 | | 4x+2[4-2(x+2)]=2x-1 | | 4(m-4)=12 | | 18.8=2(3.14)r | | 22=2l+2(7) | | Y=x^5-1x^3-6x | | 9y=-45x+45 | | -y^2+9y-9=0 | | 2x+10=20x-20 | | 5m*5m+27m+34=0 | | x=2y+2 | | 4y^2+16y+18=0 | | 3x+3=105 |